Features of provided by the Criminal Code Ukraine situation combination actions of the criminal law in space and between persons - Берзін , П. С. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
This article deals with some situations envisaged by the Criminal Code, when the action of the criminal law in space and between persons are combined. The contents of these situations depends on the legal status of persons and forms of international cooperation of the criminal proceedings. It is noted that the content of the legal status of persons associated with the existing situation of such persons, their rights and duties, and its volume is determined by specific types of people (as subjects of legal status) who are in the state (citizens of Ukraine, foreigners, stateless persons, staff of diplomatic missions and consular offices, those for which questions of extradition to a foreign country (extradition), etc.). The amount of legal status can apply to: 1) all persons residing in the state, that have general and called «common»; 2) some of these people in specifically defined situations; in which case it is called a «special»; 3) individuals in exceptional situations where it is a kind of deviations from the general and special legal status and called «exceptional.» Depending on how the combined content (volume) of the legal status of persons with specific forms of international cooperation in criminal proceedings, are allocated general, special and exceptional rules. It is substantiated that Article 10 of the Criminal Code noted criminal consequences for the persons associated only with such forms of international cooperation, as delivery of a foreign state for criminal prosecution and committal for trial, transfer of criminal proceedings and execution of foreign judgment in Ukraine court or international judicial institutions.

У статті розглядаються окремі ситуації, передбачені Кримінальним кодексом, коли дія кримінального закону в просторі та за колом осіб поєднуються. Визначається, що зміст цих ситуацій залежить від правового статусу осіб і форми міжнародного співробітництва держав під час кримінального провадження. Залежно від того, яким чином поєднується зміст (обсяг) правового статусу особи з конкретними формами міжнародного співробітництва під час кримінального провадження, виділяються загальні, спеціальні та виняткові правила. Обґрунтовується, що ст. 10 КК України кримінально-правові наслідки для відповідних осіб пов’язуються лише з такими формами міжнародного співробітництва, як їх видача іноземній державі для притягнення до кримінальної відповідальності та віддання до суду, передача кримінального провадження, а також виконання в Україні вироку іноземного суду чи міжнародної судової установи. У статті розглядається кожна із цих форм міжнародного співробітництва та їх вплив на дію кримінального закону в просторі та за колом осіб.
ОСОБЛИВОСТІ ПЕРЕДБАЧЕНИХ КРИМІНАЛЬНИМ КОДЕКСОМ УКРАЇНИ СИТУАЦІЙ ПОЄДНАННЯ ДІЇ. КРИМІНАЛЬНОГО ЗАКОНУ В ПРОСТОРІ ТА ЗА КОЛОМ ОСІБ
Keywords: criminal law; action; space; time; international cooperation.; кримінальний закон; дія; простір; час; міжнародне співробітництво.